TRANSFER TEKNOLOGI OTOMATISASI PROSES PENGOLAHAN NIRA KELAPA MENJADI GULA KELAPA PADA KELOMPOK TANI KELAPA JAYA - Fadhilah, Raudhatul; Alfian, Rudi; Gunarto; Irawan, Doddy (Universitas Mataram, 2024)
Kelapa Jaya is a peasant group that uses nira coconut to make coconut sugar. The production process is still traditional. The farmer's group is still using a manual mixer so it takes a long complaint time, six hours. Besides, the product still does not have a brand so its sales value is still low. Therefore, it is necessary to transfer technology to accelerate the production process and increase the sales value of the product. This community partnership program (PKM) aims to: (1) transfer the efficiency technology of production processes with automatic complaints. (2) increase the sales value of products with labelling and merck. This PKM uses an action or participatory approach with the PKM team acting as a trainer, accompanist, observer, supervisor, and evaluator of the success of the program carried out by the farming group. PKM results show that the automatic nira sugar mixer can accelerate the process of grinding by 17%. The device can accelerate the re-grinding process from 6 hours to 5 hours. This can happen because of the uniform grinding and heating so that the nira clamps faster. There has been an increase in the knowledge and skills of each partner by 70%. Partners have been able to increase the sales value of the product by giving the brand and label on the coconut sugar products sold. A survey of partners showed that 100% of participants were satisfied with the program. The automatic Nira mixer successfully accelerates the coconut sugar production process. Partners have been able to produce cocoa sugar products faster and sell products with attractive packaging.